The Basis for Amending the Constitution of 1979: the Legal or Political Practice of the Nation - Alireza Dabirnia (دولت‌پژوهی, 2019)
The nature of the nation practice (nation-state) in creating and amending a constitution is usually measured by two legal and political perspectives: In the legal approach, this jurisdiction is defined within a legal system, but in the political approach the jurisdiction is considered to be the basis of the constitution and the power of government derives exclusively from the political will of the nation. It appears that the Constitutional Review Council was constituted in 1989 on the basis of the political theory of "political will of the nation as the foundation of the Constitution" and that the nations ‘intended reforms was done because basically no right was included for the nation to amend the constitution in 1979. The main purpose of the present study is to examine the theoretical foundations of the competence of the nation in drafting and amending the constitution; what is more, the results of this research can be considered as one of the political theories of government in Iran. The research method is descriptive-analytical and the research question is "On what basis and the theory of the 1979 constitution has been revised and amended"? It can be argued that the constitution is credited with a basis called the political will of the nation.